Anatomo-Clinical Aspects of Male Breast Carcinoma - Raivoherivony, Zo Irène; Rakotondrainibe, Fenohery Nalisoa; Ranaivoson, Haingo Voahangy Rabetafika; Randrianjafisamindrakotroka, Nantenaina Soa (International Journal For Research In Biology & Pharmacy, 2019)
Male breast cancer is a rare pathology. It represents 1% of all male cancers. The diagnosis is often late, which makes the prognosis pejorative. The aim of our study is to describe the cytological and histo-epidemiological aspects of male breast cancer diagnosed at Anatomy and Cytology Pathology Laboratory of Joseph Ravoahangy Andrianavalona University Hospital in Antananarivo during 9 years.This is a retrospective and descriptive study, including all cases of male breast cancer, diagnosed on cytological examination, with or without histological examination.We collected 7 cases. The average age of the patients was 45 years old. The disease was revealed in all cases by a palpable mass of 20 to 40 mm long axis, unilateral in 6 cases and bilateral in one case. The diagnosis was ductal carcinoma in all cases. One case was histologically confirmed and classified as infiltrating ductal carcinoma (stage II SBR (3 + 2 + 1), stage ypT4N2Mx), with Luminal A molecular type (ER +, PR -, HER2 -).Male breast cancer is often discovered at advance stage. Cytological examination has an important place in the diagnosis.